Entrepreneurial Inclination and Organisational Performance of Kenyan Small and Medium Enterprises: The Mediating Role of Business Model Innovation - Simiyu, Albert; Ndemo, Bitange; Kinoti, Mary; Wainaina, Gituro (Archives of Business Research, 2023)
This study investigated the effect of entrepreneurial inclination on Kenyan Small and Medium Enterprises (SMEs) performance and whether this effect was mediated through Business Model Innovation (BMI). Primary data were collected from a sample of 221 SMEs that had been ranked among the Top 100 medium enterprises in Kenya between 2008 and 2019 through Klynveld Peat Marwick Goerdeler (KPMG) and Nation Media Group yearly surveys. Data accepted from 134 top executives of the SMEs was analysed through regression analysis. The results revealed that entrepreneurial inclination indirectly influenced organisational performance through its positive effect on BMI. There was no evidence that entrepreneurial inclination independent of BMI influenced organisational performance. Thus, it was concluded that entrepreneurial inclination positively contributed to organisational performance through its favourable effect on BMI. The study adds to the literature on entrepreneurial inclination and organisational performance by linking them to BMI. The study advises industry practitioners and policymakers to encourage entrepreneurial conduct and BMI practices to improve organisational performance. Further studies are required to address the identified gaps.